Does the green economy really foster food security in Sub-Saharan Africa? - Somlanare Romuald Kinda (Cogent Economics & Finance, 2021)
Over the last decade, the green economy concept has emerged as a fundamental policy framework for sustainable development in developing countries. This paper contributes to the current debate by providing an empirical investigation of the effect of the green economy on food security in 35 Sub-Saharan African countries for the period of 2001-2015. The results provide evidence that green economy indicators have controversial effects on food security (food availability and the proportion of undernourished people). Indeed, the results show that biofuels contribute to decreased food security in Sub-Saharan African countries, whereas renewable energy improves food security. Carbon dioxide emissions have no effect on food security. The results are robust to alternative robustness checks, such as the two-step Generalized Method of Moments (GMM) system.
Keywords: 330; Africa (N57); food security (Q18); Green economy (O44)